Contact force-guided catheter ablation for the treatment of atrial fibrillation: a meta-analysis of randomized, controlled trials - Qi,Z. (2016)
Contact force (CF) sensing technology allows real-time monitoring during catheter ablation for atrial fibrillation (AF). However, the effect of CF sensing technology on procedural parameters and clinical outcomes still needs clarification. Because of the inconsistent results thus far in this area, we performed a meta-analysis to determine whether CF sensing technology can improve procedural parameters and clinical outcomes for the treatment of AF. Studies examining the benefits of CF sensing technology were identified in English-language articles by searching the MEDLINE, Web of Science, and Cochrane Library databases (inception to May 2015). Ten randomized, controlled trials involving 1834 patients (1263 males, 571 females) were included in the meta-analysis (681 in the CF group, 1153 in the control group). Overall, the ablation time was significantly decreased by 7.34 min (95%CI=-12.21 to -2.46; P=0.003, Z test) in the CF group compared with the control group. CF sensing technology was associated with significantly improved freedom from AF after 12 months (OR=1.55, 95%CI=1.20 to 1.99; P=0.0007) and complications were significantly lower in the CF group than in the control group (OR=0.50, 95%CI=0.29 to 0.87; P=0.01). However, fluoroscopy time analysis showed no significantly decreased trend associated with CF-guided catheter ablation (weighted mean difference: -2.59; 95%CI=-9.06 to 3.88; P=0.43). The present meta-analysis shows improvement in ablation time and freedom from AF after 12 months in AF patients treated with CF-guided catheter ablation. However, CF-guided catheter ablation does not decrease fluoroscopy time.